Perceptions about a pharmacy-delivered weight management service in community pharmacy settings in Jordan - Ghaith Al-Taani, Rasha Arabyat, Rimal Mousa (Journal of Applied Pharmaceutical Science, 2024)
Treatment of obesity is a public health priority. Despite the effectiveness of anti-obesity interventions, they are not currently offered by pharmacists and have not been included in reimbursement plans. The present study aimed to investigate the public perception of a pharmacist-led weight-management program. A convenient sample of individuals in a large city in northern Jordan completed a pretested short survey to assess their accessibility, perception, and willingness to pay (WTP) for weight-management services offered by community pharmacists. WTP for pharmacy-delivered weight management services was assessed using a payment card approach with a hypothetical scenario. The validity and reliability of the instrument were also assessed. Factors affecting WTP and respondents’ beliefs about weight management services by pharmacists were assessed using chi-square, Kruskal Wallis, and logistic regression analysis. A sum of 966 questionnaires (response rate 96.6%) were included in the analysis. A total of 71.2% of respondents indicated that community pharmacy weight-reduction services were useful or very useful. Some of the respondents had limitations in access to weight management services delivered by nonpharmacists, in terms of the inconvenience of the location (61.5%) and difficulty in visiting a dietician (26.3%). Although 14.8% were not willing to pay for pharmacist services, 20.4% would pay $5, 20.4% would pay $10, 11.9% would pay $15, 14.2% would pay $20, 9.8% would pay $30, and 14.4% would pay $50. Independent significant predictors of WTP for weight management services, as indicated by logistic regression of WTP for weight management services included, were having four or more family members [odds ratio (OR) = 2.00], considering community pharmacists’ obesity-reduction intervention as useful or very useful (OR = 2.1), and having average, high, or very high standards of living (OR = 1.9). Most of the respondents had favorable attitudes and were willing to pay for pharmacists’ delivered obesity interventions. More than one-third of respondents were willing to pay an amount that is more than $15. Such findings are promising in justifying the addition of new services delivered by community pharmacists. Future research should be expanded to other regions to improve the generalizability of results.
Keywords: Community pharmacy, Jordan, obesity, weight management service, pharmacy service, willingness to pay, perception, belief, survey